Strategi Transformasi Pembelajaran Akidah dan Akhlak dalam Pembentukan Karakter Islami di Era Society 5.0 - Halimah; Mayasari; Ali Maulida (IEC: Journal of Educational Innovation, 2026)
This study is motivated by the paradigm shift in Islamic education in the era of Society 5.0, which requires the integration of digital technology and spiritual values in Akidah Akhlak learning. The rapid development of information technology has significantly influenced students’ learning patterns, necessitating learning strategies that balance technological competence and Islamic character formation. The aim of this study is to analyze the transformation strategies of Akidah Akhlak learning, examine the integration of digital technology in shaping Islamic character, and identify supporting factors, barriers, and implementation solutions in the Society 5.0 era. This research employs a Systematic Literature Review (SLR) with a qualitative-descriptive approach using thematic analysis of various reputable academic sources. The findings indicate that the transformation of Akidah Akhlak learning leads to adaptive, human-centered, and technology-based learning models such as blended learning and project-based learning. The integration of digital technologies such as Learning Management Systems, interactive media, and artificial intelligence enhances the internalization of Islamic character values. The main supporting factors include digital infrastructure, teacher competence, and educational policies, while the main barriers are gaps in digital literacy, limited facilities, and resistance to conventional pedagogy. Proposed solutions include teacher training, strengthening the Society 5.0 curriculum, and developing hybrid learning models. The novelty of this study lies in the development of a holistic transformation strategy for Akidah Akhlak learning that integrates Islamic pedagogy, digital technology, and Islamic character within the framework of Society 5.0. The implication of this study is the need for educational reform based on digital transformation while maintaining Islamic spiritual values.